2018
DOI: 10.1080/1547691x.2018.1532974
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin receptor in immune-mediated renal tubular injury in trichloroethylene-sensitized mice: Impact on NF-κB signaling pathway

Abstract: xing Zhu (2018) Bradykinin receptor in immune-mediated renal tubular injury in trichloroethylene-sensitized mice: Impact on NF-κB signaling pathway, Journal of Immunotoxicology, 15:1, 126-136, ABSTRACT Trichloroethylene (TCE) is known to induce skin disorders and multi-system dysfunction, but the mechanism of this multi-organ injury is not entirely clear. It was shown in a previous study that levels of pivotal end-products of the kallikrein-kinin system (KKS), i.e. bradykinin (BK) and BK receptors B1R/B2R, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
1
3
0
1
Order By: Relevance
“…Consistently, our previous studies have also found that pathological changes in the kidney and impairment of renal function in TCE sensitized mice (Yang et al, 2018).…”
Section: Introductionsupporting
confidence: 90%
“…Consistently, our previous studies have also found that pathological changes in the kidney and impairment of renal function in TCE sensitized mice (Yang et al, 2018).…”
Section: Introductionsupporting
confidence: 90%
“…У фібробластах вульви БK/B2R індукує активацію NF-κB, що посилює вивільнення IL-6 і викликає біль [35]. У суглобових хондроцитах людини та епітеліальних клітинах нирок БK індукує вивільнення запальних цитокінів, таких як IL-6 та IL-8, за допомогою сигнального механізму NF-κB [36]. [41,42], який призводить до розширення судин, збільшення проникності судин і гіпотензії.…”
Section: участь у процесах запаленняunclassified
“…Based on the high expression of HMGB1 in lung tissues of COPD mice, the downstream NF-κB pathway of HMGB1 was investigated. The degradation of IκB and increased phosphorylation of IκB protein are the main manifestations of the activation of the NF-κB pathway [Yang et al, 2018;Chu et al, 2020]. The protein levels of p-IκBα and IκBα in lung tissues of COPD mice were tested by western blot.…”
Section: Hmgb1 Promoted Inflammatory Responses By Activating the Nf-κ...mentioning
confidence: 99%